COUNSELING ON MENTAL HEALTH AWARENESS OF CHILDREN OF THE NATION - Isabel Lamasigi, Adinda Widya; Rahmanissa, Shafira; Aprilia Iriani, Lovita Angeli; Putra, Nabil Irfani (Universitas Muhammadiyah Tapanuli Selatan, 2022)
Human mental health has the same position as physical health. If one's mental health is stable, their other aspects of life may function more optimally. Adolescent mental health is one of the critical factors in advancing the quality of the nation. In addition, intelligence in regulating emotions can help balance children's mental health, especially in dealing with life problems in their environment. However, the emergence of the COVID-19 pandemic, which requires adolescents to stay at home, impacts their behavior by reducing social interaction and therefore makes them experience boredom. The strategy to expand knowledge regarding mental health is first conducting research to determine what impacts are often felt by children of the nation due to mental health disorders, then providing counseling on prevention, characteristics, causes, and treatment of mental health disorders through Instagram accounts of each author. Causes and prevention of mental health disorders of children of the nation can be collected from the support of references. This condition prompted the author to carry out counseling in mental health awareness and as a forum of aspirations to expand mental health policies in Indonesia. The study results stated that two-thirds of the respondents experienced mental health disorders that may require medical attention. This becomes very dangerous for the mental health of children of the nation because it can impact children's self-development and daily life; children encounter learning difficulties because they are not able to fully concentrate on learning, behave deviantly in the school environment, thereby increasing the number of delinquency and crime in adulthood (Malfasari et al., 2020). Counseling can increase knowledge about people's mental health (Rohayati, 2021). According to the data obtained, it is currently necessary to carry out counseling to make adolescents aware of the importance of mental health and contribute to advancing the nation.Â